Acute sialadenitis with acute myocarditis - Muhammad Dwijo Murdiyo; Siregar, Solita Vasya (Oto Rhino Laryngologica Indonesiana, 2025)
Background: Acute sialadenitis is an inflammation in the salivary glands that can be caused by various factors. This condition can also lead to complications beyond the head neck region, such as meningitis, pancreatitis, myocarditis, anemia hemolytic anemia, polyarthritis, and neck abscess. Purpose: To understand the clinical symptom, cause, and complications, that could occur in acute sialadenitis. Case report: A 65 years old man came to the hospital with swelling of the neck, chest pain, and salivary glands inflammation, along with findings suggestive of acute myocarditis. Clinical question: What complications can occur in sialadenitis? Method: A literature search was carried out on the Google Scholar site, in February-March 2022, with keywords “Sialadenitis” AND “Sialadenitis Complications” AND “Acute Myocarditis”. The inclusion criteria were publications in the last 20 years that were relevant to the topic, and had a full manuscript available. Result: There were 19 literatures obtained, and all could be used as a reference. Conclusion: The complications of sialadenitis were determined based on symptoms and comprehensive diagnostic tools, and the management needed multidemensional department collaboration.